Seafarers' mental health and wellbeing - pose covid and beyond - Lim, Priscilla Jia Qian (Nanyang Technological University, 2023)
Purpose: The purpose of the research is to investigate the impact of the technostress framework on several aspects of seafarers' mental well-being and, as a result, turnover intention. Utilising an exploratory factor analysis, the following five factors were identified: job security threat, technical developments, IT assistance, technological implementation, and technological onboarding. Design/methodology/approach: To analyse the essential aspects, factor analysis was applied to summarise job security threats, technology developments, IT support, technological implementation, and technological onboarding. For evaluating the internal consistency of the survey replies, reliability tests based on Cronbach's alpha and adjusted item-total correlation coefficients were performed. The ANOVA test was used to determine if there were any variations in respondents' perceptions of these elements based on their demographics. The association between technostress creators, technostress inhibitors, burnout, self-efficacy, social isolation and loneliness, and turnover intention was investigated using multiple regression model analysis. Findings: Results revealed that while both technostress creators and inhibitors have a positive relationship with burnout, only technostress inhibitors significantly impact burnout. Meanwhile, while technostress creators and social-isolation and loneliness have an inverse relationship with self-efficacy, technostress inhibitors have a positive impact on self-efficacy. Furthermore, all factors such as technostress creators, technostress inhibitors and burnout have a negative correlation with social-isolation and loneliness. Lastly, turnover intention is significantly impacted by social isolation and loneliness negatively. Originality/value: This study has highlighted the significance of the technostress framework in the context of burnout, self-efficacy, social isolation and loneliness, and turnover intention in the maritime setting. The findings have far-reaching ramifications for maritime companies and employers of seafarers. Keywords: Technostress, burnout, self-efficacy, social isolation and loneliness, and turnover intention